Renarasi Teks Alkitab bagi Anak Usia Dini dengan Teknologi Metaverse - Yane Octavia Rismawati Wainarisi (TEMISIEN: Jurnal Teologi, Misi, dan Entrepreneurship, 2023)
Entire World had reshock with the metaverse since Mark Zuckerberg claim to rebranding Facebook to MetaÂ  in 2021, November. This Metaverse term is not a new term in digital world because since its emergence, there are many digital manufacture effort to create innovation by meta technology. The development technology of Meta influence all human activities in all circle of life include spiritual activities in early Childhood to renarrative the Bible Text in their context. Because of this reason, the Church try to use Meta technology in ministry service so the early childhood can get full description about the World in Biblical Setting. This research made by explanative qualitative method with comparative analysis to early childhood Sunday School Student in Three different church with different social context.